Avaliação da resistência à tração de pinos de fibra de vidro: influência do tipo de tratamento de superfície empregada ao pino - Matsusita, Talita [UNESP] (2011)
The intraradicular pins are shown to promote a framework upon which the coronal restoration may be retained. The pins also have fiberglass modulus of elasticity similar to dentin, and studies show that they better distribute masticatory forces in root dentin, reducing the risk of fractures, besides their natural translucency, which makes for an excellent cosmetic result. To achieve success in the use of prefabricated intrarradicular pins, the selection of the luting agent is crucial. The objective of this study was to evaluate the tensile strength of reinforced fiberglass with different surface treatments cemented in bovine incisors. After extraction, the bovine incisors were stored in aqueous 2% formaldehyde, pH 7 for 30 days, then scraped with number 11-12 periodontal curettes and cleaned with a jetspray mixture of baking soda and water. After the teeth were stored in 0.9% saline solution, and held a selection of teeth with straight roots and the like. The teeth were sectioned into 17mm pieces, obtaining standardized root. This was done in order to obtain dimensions similar to each other. We discarded the teeth that had root canal widths greater than the Largo drill No. 5. After selection, the teeth were filled and prepared their pipes at a depth of 12 mm. After partial removal,, the pipes and glass fiber posts were prepared for adhesive cementation according to the indication of the manufacturer. After cementation of fiber posts were carried out, a tensile test in a universal testing machine - EMIC - DL 3000 model with axial tensile loading speed of 0.5 mm / min was conducted. The data collected was subjected to analysis of variance (ANOVA) and Tukey tests. The data collected were subjected to analysis of variance (ANOVA) and Tukey test. Control group (49.96) presented the medium of higher tensile strength, followed by group 2 (alcohol, phosphoric...